Unveiling the nexus between solar energy adoption and crop farmer income: evidence from Pakistan - Khan, Nawab; Elhindi, Khalid M.; Kassem, Hazem S.; Kazim, Rizwan; Zhang, Shemei (Frontiers in Sustainable Food Systems, 2024)
Worldwide, the continuous advancement of off-grid solar photovoltaic irrigation seeks to improve water access, increase food production, and reduce carbon emissions and energy costs associated with fuel usage. Consequently, this enhances human resilience to climate change and contributes to the improvement of farmers’ income. This study investigates the influence of solar energy adoption on farmers’ income, drawing insights from 1,080 growers in Pakistan. It uses the logit model and propensity score matching (PSM) to address bias. Factors influencing income, including gender, education, decision-making autonomy, farm size, extension services, cooperative associations, access to credit, risk perception, market distance, and tube well availability, are identified. Findings reveal a positive correlation between solar energy adoption and increased crop farmer income. PSM analysis validates this, emphasizing the need for government and agricultural extension interventions to enhance financial accessibility for farmers facing mobility challenges. This includes subsidies for technology adoption and knowledge dissemination about digital technology. The study advocates for an accelerated adoption of solar energy to foster agricultural development in Pakistan. In resource-poor nations like Pakistan, government subsidies are crucial to offset technology costs for citizens facing challenges in affording green energy. Addressing Pakistan’s energy crisis through promoting solar energy for irrigation can amplify farmers’ income. It is imperative to promote access to this technology, particularly for water pumping, through subsidies and readily available credit facilities, given the resource limitations and small landholdings of many farmers in Pakistan.